Spray gel film-forming system formulation of Vernonia amygdalina as diabetic wound healer - Novitasari, Putri Rachma; Nuari, Yudha Rizky; Firdausi, Azzahro Aulia (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Poorly managed diabetes mellitus may elevate the risk of having a diabetic wound that may lead to non-traumatic lower limb amputation. Therefore, wound healing management in diabetic patients is essential to prevent such complications. African leaves (Vernonia amygdalina) has been widely used for wound treatment empirically for years including diabetic wounds. The current study focuses on developing an African leaves-based spray using a film-forming system for diabetic wound healing. The African leaves extract is formulated with polyvinyl alcohol (PVA) to create a viscous liquid and is then made into a spray gel-film form. The spray gel film formulation was further characterized and tested for its wound closure efficacy in animal testing. The characterization include watery form, green colour and a characteristic odour of African leaf extract. The spray gel film preparation of Vernonia amygdalina 1;2;4% extract have pH of 5.92±0.0011; 5.96±0.0011 and 5.42±0.0011. The viscosity value of the spray gel film 1;2 and 4% were 7.98±0,0012; 8.43±0.0019 and 5.70±0.0013 cPs. Dry time of Spray Gel Film of Vernonia amygdalina 1;2;4% extract were 1.47±0.0013; 1.50±0.0010; and 1.56±0.0010 minutes. The wound healing was evaluated using diabetic Wistar rats by measuring daily wound diameter. The result showed at a concentration 1%; 2%; 4% the percentage diameter of wound healing were 81.52±±0.06; 82.28±±0.05; and 100±±0.00 %. They were effective for wound healer in diabetic rats and it had antibacterial activities.